In What Sense is La Cuarta a “Popular” Newspaper? - Santa Cruz Achurra, Eduardo (Universidad de Chile. Instituto de la Comunicación e Imagen, 2010)
The paper seeks to problematize concept of "Popular" that characterizes the discourse of Chilean newspaper La Cuarta. With this purpose, it reviews some of the ways the popular manifests historically in Chile and then analyzes how these historical senses are recontextualized by the newspaper La Cuarta within a mediated, massive and post-dictatorship society.